1998
DOI: 10.1148/radiology.208.2.9680570
|View full text |Cite
|
Sign up to set email alerts
|

Subarachnoid space disease: diagnosis with fluid-attenuated inversion-recovery MR imaging and comparison with gadolinium-enhanced spin-echo MR imaging--blinded reader study.

Abstract: FLAIR is highly sensitive and specific for the diagnosis of SAS disease. Unenhanced FLAIR is superior to gadolinium-enhanced T1-weighted MR imaging for the diagnosis of SAS disease. These data have important implications, because FLAIR is performed without the costs and inherent risks of intravenous contrast agents. FLAIR also appears to be highly sensitive but nonspecific for acute SAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(70 citation statements)
references
References 0 publications
0
67
0
3
Order By: Relevance
“…This type of lymphoma extends along the Virchow Robin space, so may be identified as an intradural extraaxial lesion by fluidattenuated inversion recovery imaging. 41) Hypertrophy of the posterior longitudinal ligament, which is located on the ven tral side of the spinal cord, appears isointense to the cord on T 1 weighted imaging and is only slightly enhanced by GdDTPA administration as a thin irregular venous plexus in the lesion. Hypertrophy of the ligamentum flavum, which is located on the dorsal side of the spinal cord, shows similar findings to hypertrophy of the posterior longitudinal liga ment without enhancement.…”
Section: Resultsmentioning
confidence: 99%
“…This type of lymphoma extends along the Virchow Robin space, so may be identified as an intradural extraaxial lesion by fluidattenuated inversion recovery imaging. 41) Hypertrophy of the posterior longitudinal ligament, which is located on the ven tral side of the spinal cord, appears isointense to the cord on T 1 weighted imaging and is only slightly enhanced by GdDTPA administration as a thin irregular venous plexus in the lesion. Hypertrophy of the ligamentum flavum, which is located on the dorsal side of the spinal cord, shows similar findings to hypertrophy of the posterior longitudinal liga ment without enhancement.…”
Section: Resultsmentioning
confidence: 99%
“…This conclusion was based upon improved sensitivity of MRI for lesion detection from 99.5% using FLAIR images alone to 99.6% after inclusion of postcontrast sequences. Previous studies in humans also have suggested that negative FLAIR images may eliminate the need for gadoliniumā€enhanced T1W images in the diagnosis of intracranial infections,17 leptomeningeal disease,18 and in the detection of intracranial tumors 19, 20. However, a critical review of the human literature concluded that despite the widespread use of MR contrast media, no rigorous studies existed to establish a solid evidence base for their application in human medicine 1…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] This relies on the fact that FLAIR imaging is designed to null the normal CSF signal intensity, and any alteration in the CSF results in an increased signal intensity in the CSF. Postgadolinium FLAIR imaging has also shown hyperintensity in the SAS in patients with pathologies that are not specific to the SAS but rather disrupt the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%